2017
DOI: 10.1371/journal.pone.0173893
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CD4 and CD8 dynamics and viral rebounds on loss of virological control in HIV controllers

Abstract: ObjectiveHIV controllers (HICs) spontaneously maintain HIV viral replication at low level without antiretroviral therapy (ART), a small number of whom will eventually lose this ability to control HIV viremia. The objective was to identify factors associated with loss of virological control.MethodsHICs were identified in COHERE on the basis of ≥5 consecutive viral loads (VL) ≤500 copies/mL over ≥1 year whilst ART-naive, with the last VL ≤500 copies/mL measured ≥5 years after HIV diagnosis. Loss of virological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“… have reported in HIV controllers with a plasma viral load below 1000 copies/mL that the percentage of CD4 and CD8 T cells expressing the markers HLA‐DR and CD38 in the blood as well as in the GALT decreased after 24 weeks of ART. Accordingly, another study observed, also in controllers, that blips are associated with a drop in CD4/CD8 ratio, a global marker of immune activation . These observations fit with the hypothesis that reducing viral production at low levels may prevent immune activation.…”
Section: The Issue Of Inflammation and Immune Activationsupporting
confidence: 67%
“… have reported in HIV controllers with a plasma viral load below 1000 copies/mL that the percentage of CD4 and CD8 T cells expressing the markers HLA‐DR and CD38 in the blood as well as in the GALT decreased after 24 weeks of ART. Accordingly, another study observed, also in controllers, that blips are associated with a drop in CD4/CD8 ratio, a global marker of immune activation . These observations fit with the hypothesis that reducing viral production at low levels may prevent immune activation.…”
Section: The Issue Of Inflammation and Immune Activationsupporting
confidence: 67%
“…In one multinational observational study of individuals followed from seroconversion (CASCADE), virus control (<500 copies RNA/mL) occurred in a small minority (1.4%) but once achieved was maintained in most (the probability of maintaining control over 20 years was 0.74) [ 11 ]. In a multicenter study of controllers (Collaboration of Observational HIV Epidemiological Research Europe [COHERE]), progression was rare and was predicted by a low CD4/CD8 ratio and intermittent viremia [ 67 ]; similar findings were noted in a French study [ 68 ]. In smaller pathogenesis-oriented studies, heightened inflammation and T-cell activation predated and often predicted virologic progression [ 17 , 69 , 70 ].…”
Section: Can We Learn Anything From Controllers Who Eventually Progrementioning
confidence: 76%
“…Few studies have examined the long-term outcome of LTNP and HIC patients [ 2 9 ]. Contrary to previous studies, we used competing-risk analysis to accurately estimate the risk of status loss while avoiding overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Although many definitions coexist [ 1 ], these patients are generally defined as either long-term non progressors (LTNP) or HIV controllers (HIC), depending on whether they are defined based on immunologic or virologic factors and on protection of AIDS-defining events in the absence of antiretroviral treatment. Few studies have focused on the long-term outcomes of such rare patients [ 2 9 ], who will become more difficult to identify as new treatment guidelines recommend treatment initiation as early as possible. Therefore the management of the individuals already identified with such status is an issue for both patients and caregivers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%